EFFECTS OF CORPORATE GOVERNANCE VARIABLES ON EARNINGS MANAGEMENT IN INDONESIA - Stephanus Remond Waworuntu; Marko Sebira Hermawan; Sheila Nerissa Hokardi (Jurnal Keuangan dan Perbankan, 2012)
To determine the effects of corporate governance on earnings management, this paper analyzed 171 annualreports from issued 2006 to 2009 by 57 non-financial, joint stock companies implementing GCG (GoodCorporate Governance) practices, which were listed on the Indonesia Stock Exchange (IDX). Six corporategovernance variables (board composition, independent commissioners, separate chairman/CEO roles, auditcommittee, managerial share ownership, and audit quality) as well as three control variables (leverage, size,and ROA) were used. The results showed that two corporate governance variables significantly influencedearnings management practices (separate chairman/CEO roles and managerial share ownership); the othervariables had no effect because these companies used GCG practices only to follow regulations rather than tomonitor and control.